350 Jaar Gereformeerd 1652-2002. Kerkreg en kerkregering in die NG Kerk gedurende die afgelope dekades - Coertzen, P (Nederduitse Gereformeerde Teologiese Tydskrif, 2015)
The article describes and evaluates certain aspects of the order in the Dutch Reformed Church during the past few decades. The aspects which are described and evaluated are: the nature of the church polity and government in the Dutch Reformed Church; developments regarding the Church Order; development with regard to the offices in the Church; labour relations, and church orderly development with regard to church unity.